Answer:
So Equation ( 1 ) is NOT Equivalent to Equation ( 2 )
Step-by-step explanation:
Given:
..............Equation ( 1 )
................Equation ( 2 )
To Find:
Whether Equation ( 1 ) is Equivalent to Equation ( 2 )
Support your answer by evaluating the expression for t = 2.
Solution:
For t=2 Equation ( 1 ) we get
![11t - 4t=11(2) - 4(2)=22-8=14](https://tex.z-dn.net/?f=11t%20-%204t%3D11%282%29%20-%204%282%29%3D22-8%3D14)
For t=2 Equation ( 2 ) we get
![4t - 11t=4(2) -11(2)=8-22=-14](https://tex.z-dn.net/?f=4t%20-%2011t%3D4%282%29%20-11%282%29%3D8-22%3D-14)
From above we get two different values
So Equation ( 1 ) is NOT Equivalent to Equation ( 2 )